2017
DOI: 10.1002/cplu.201600519
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Interfaces in Heterostructures

Abstract: Nanocomposites represent an interesting class of materials because their applications are of multidisciplinary importance. Herein, interactions at the interface of heterostructures, leading to superior performance and sometimes to synergistic interactions, are highlighted. Although the types of junctions seem to be similar in different fields, the requirements for their function is device‐dependent and thus no generally valid recipe can be utilized. Nonetheless, the overlap between research fields unveils the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 201 publications
(200 reference statements)
0
15
0
Order By: Relevance
“…At the same time, effective separation of the electrons and holes can also be achieved by the space charge region established owing to the gradient of carrier concentration at the interface. [37][38][39][40][41] Raising the annealing temperature tends to eliminate the surface state as well as promoting the pyrolysis of copper acetate, which makes the space charge region more dominant, leading to more effective charge storage.…”
Section: +mentioning
confidence: 99%
“…At the same time, effective separation of the electrons and holes can also be achieved by the space charge region established owing to the gradient of carrier concentration at the interface. [37][38][39][40][41] Raising the annealing temperature tends to eliminate the surface state as well as promoting the pyrolysis of copper acetate, which makes the space charge region more dominant, leading to more effective charge storage.…”
Section: +mentioning
confidence: 99%
“…In the past few decades, several methods [2][3][4] have been developed to overcome the serious shortcomings of fast charge recombination and limited visible-light absorption of semiconductor photocatalysts. One of the most widely explored strategies is the use of photocatalytic heterojunctions [2,[5][6][7]. Previous work [8,9] has demonstrated that the construction of two semiconductors with suitable electronic structures may exhibit superior photoactivity than single photocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the formation of heterostructures would also introduce defects at the interfaces as new recombination centers for photogenerated charge carriers, leading to reduced activities . Therefore, fine tuning of the interfacial properties of heterostructured photocatalysts through optimization of the synthetic methods and the introduction of passivating/mediating layers is very important for the performance enhancement …”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…[101] Therefore, fine tuning of the interfacial properties of heterostructured photocatalysts through optimization of the synthetic methods and the introduction of passivating/mediating layers is very important for the performance enhancement. [102] Since heterostructured hollow photocatalysts show outstanding properties for photocatalytic water splitting and CO 2 reduction, it is essential to further explore this research field perhaps from the following aspects: 31,1900281 materials for energy-related applications, novel designs may be achieved by MOF-based synthetic approaches. [36,103] For instance, hollow photocatalysts with homogenous heterojunctions could be fabricated by post conversion of MOF materials with multiple metal nodes.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%